2016
DOI: 10.1097/mcp.0000000000000318
|View full text |Cite
|
Sign up to set email alerts
|

Oronasal mask may compromise the efficacy of continuous positive airway pressure on OSA treatment

Abstract: Nasal CPAP must be the first choice to treat OSA. Patients on oronasal mask should be carefully followed. VIDEO ABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…Our findings are particularly relevant in the light of the impact of the choice of interface on residual AHI. Oronasal masks may exacerbate or cause upper airway obstruction due to posterior displacement of the jaw and the tongue . Large observational studies and a recent RCT have demonstrated that residual AHI was lower with nasal masks than with oronasal masks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are particularly relevant in the light of the impact of the choice of interface on residual AHI. Oronasal masks may exacerbate or cause upper airway obstruction due to posterior displacement of the jaw and the tongue . Large observational studies and a recent RCT have demonstrated that residual AHI was lower with nasal masks than with oronasal masks.…”
Section: Discussionmentioning
confidence: 99%
“…Oronasal masks may exacerbate or cause upper airway obstruction due to posterior displacement of the jaw and the tongue. 25 Large observational studies 11 and a recent RCT 26 have demonstrated that residual AHI was lower with nasal masks than with oronasal masks. A recent meta-analysis summarizing these findings showed that oronasal masks were associated with greater CPAP pressure levels, higher residual AHI and poorer adherence than nasal masks.…”
Section: Figurementioning
confidence: 99%
“…15 Nasal mask have been suggested to be more effective than oronasal masks in treating OSA, perhaps since the oral portion of the oronasal mask pushes the tongue backwards, thus blocking the pharynx. 79,80 The main disadvantage of CPAP lies in its adherence. Some studies have reported an adherence rate of only 29-68%, [81][82][83][84] and adherence does not seem to have improved over a 20-year period despite behavioral interventions and improvements in machine technology.…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…Although CPAP by oral mask for OSA has been reported in some small-scale studies to be as effective as CPAP by nasal mask 13,14 , oral masks are not popular in clinical practice 15 and have not been studied in stroke patients. Therefore, looking for alternative treatments for OSA in dysphagic stroke patients requiring nasogastric tube feeding is warranted.…”
mentioning
confidence: 99%